Analisis Pengaruh Promosi pada Media Sosial, Digital Branding dan Influencer Marketing Terhadap Purchase Intention Jasa Perjalanan Wisata Mancanegara - Ibrahim, Mozart Malik; Nurbakti, Rezky; Purwati, Sri; Santosa, Muhammad Hery; Mulyana, Hadi; Nugraha, Jefri Putri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study examines how influencer marketing, digital branding, and social media promotion affect consumers' intentions to buy foreign travel services. Due to shifts in customer behavior in the digital age, digital marketing tactics are now crucial for influencing decisions about what to buy. Two hundred fifty respondents interested in traveling abroad and frequent social media users made up the study's sample. Multiple linear regression was the analysis technique to ascertain how each independent variable affected the dependent variable. The findings demonstrated that purchase intention was highly impacted by all three independent variables simultaneously. Influencer marketing was somewhat more powerful than digital branding and social media promotion. This demonstrates how crucial prominent figures are in creating favorable opinions about tourism services. Players in the tourism sector should use these findings as a guide when creating focused and successful marketing campaigns in the current digital environment.